2023
DOI: 10.1111/cns.14116
|View full text |Cite
|
Sign up to set email alerts
|

Folic acid deficiency exacerbates the inflammatory response of astrocytes after ischemia‐reperfusion by enhancing the interaction between IL‐6 and JAK‐1/pSTAT3

Abstract: Aim To demonstrate the role of IL‐6 and pSTAT3 in the inflammatory response to cerebral ischemia/reperfusion following folic acid deficiency (FD). Methods The middle cerebral artery occlusion/reperfusion (MCAO/R) model was established in adult male Sprague‐Dawley rats in vivo, and cultured primary astrocytes were exposed to oxygen‐glucose deprivation/reoxygenation (OGD/R) to emulate ischemia/reperfusion injury in vitro. Results Glial fibrilla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Another study found that folic acid deficiency promotes IL-6/JAK-1/pSTAT3 interactions in astrocytes after ischemia-reperfusion. So, folic acid-biofunctionalized nanocarriers may be another approach to improving targeting precision [ 86 ]. Further, the PEGylation of NPs reduces the interaction with serum proteins and enhances the stability of the nanocarrier in the reticuloendothelial system [ 87 ].…”
Section: Drug Delivery Constraints In Lung Cancer Managementmentioning
confidence: 99%
“…Another study found that folic acid deficiency promotes IL-6/JAK-1/pSTAT3 interactions in astrocytes after ischemia-reperfusion. So, folic acid-biofunctionalized nanocarriers may be another approach to improving targeting precision [ 86 ]. Further, the PEGylation of NPs reduces the interaction with serum proteins and enhances the stability of the nanocarrier in the reticuloendothelial system [ 87 ].…”
Section: Drug Delivery Constraints In Lung Cancer Managementmentioning
confidence: 99%
“…Folic acid, a type of B vitamin essential in the regular human diet, is strongly associated with neuroinflammation [ 210 ]. It is also key for the development and function of the nervous system [ 86 ] and has been shown to have an antioxidant and a neuroprotective role [ 211 ].…”
Section: Natural Antioxidant Bioactive Molecules Against Myocardial I...mentioning
confidence: 99%
“…In addition, another study, using a model of in vivo rats, as well as an oxygen–glucose deprivation/reoxygenation astrocyte cell model, found that in the context of ischemia–reperfusion, folic acid deficiency may develop an inflammatory response via the IL-6/JAK-1/phospho-STAT3 (pSTAT3) pathway on astrocytes, potentially leading to secondary brain injury. Therefore, folic acid supplementation was suggested as a potential preventive and therapeutic strategy to reduce brain damage in IS [ 210 ].…”
Section: Natural Antioxidant Bioactive Molecules Against Myocardial I...mentioning
confidence: 99%